A Systematic Review of the IoT in Smart University: Model and Contribution - Senny Luckyardi; Ratih Hurriyati; D. Disman; Puspo Dewi Dirgantari (Universitas Pendidikan Indonesia, 2022)
The objectives of the review were to identify different implementation aspects of the Internet of Things (IoT) in Smart Universities (SU) from diverse studies, amplify the theories behind the IoT utilization and model in SU; as well as offer recommendations for future research in this area. This study employed a systematic literature review (SLR) technique, conducting comprehensive searches of the most relevant articles to the research question published from 2018 to 2022. Following a review of peer-reviewed journals, a total of 69 refereed articles were chosen and analyzed. The findings of this study suggest that the technology model needs to be aligned and integrated with organizational processes. IoT utilization should meet the adoption readiness of a university. The results also revealed that the creation of SU can be divided into three categories: behavior, learning, educational technology, and physical facilities. However, the literature related to IoT utilization and model is still incoherent and lacking in theoretical frameworks that reflect on specific circumstances such as SU. SU research is still in its early stages, with more work to be done in terms of identifying technology model adoption. The review also contributed to serving as inspiration and a point of reference for institutions as they work with the smart university initiative to create a teaching and learning environment that is more effective and efficient.